Ethnic Enclave as Social and Economic Phenomenon in Today’s Russia - T. A. Bazhan (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the problem of ethnic immigrant enclave in today’s Russia. Possibility of stable and closed communities rise is stipulated not only by mass inflow of migrants of different cultures and their concentration in certain regions but also by underdeveloped state policy in the field of migration and inter-ethnic relations. In this way risks raised by enclaves are underestimated. Insufficient attention is paid to researching features of their economic activity, mainly in the shadow sector. Among economic, political, legal and social reasons that envisage possibility of enclave formation the absence of socio-cultural adaptation and integration of foreign migrants is of utmost importance. Therefore, goals of this work in the field of integration are vague, objectives are unclear, expected results are hazy and results are negative. The article studies assessment of this phenomenon given in documents of strategic planning. Different approaches to understanding the enclave and its characteristics were analyzed; conditions of enclave forming in view of current migration situation and specific features of economic, political and socio-cultural development of our society were investigated and the problem of the enclave in connection with risks and threats caused by its existence were studied. Current signs of the enclave were specified and supplementary indicators were identified as they can be formed in the Russian situation; reasons for its rise and conditions providing its existence were found. On the basis of studying the approaches to researching this phenomenon and diagnostics of ethnic community as an enclave propositions were elaborated for the complex interdisciplinary investigation, whose results could be necessary for the development of state migration policy and struggle against ethnic migrant enclave formation. Apart from that, suggestions for correcting conditions causing formation and development of ethnic migrant enclaves were put forward.